2021
DOI: 10.1371/journal.pcbi.1009644
|View full text |Cite
|
Sign up to set email alerts
|

Engaging biological oscillators through second messenger pathways permits emergence of a robust gastric slow-wave during peristalsis

Abstract: Peristalsis, the coordinated contraction—relaxation of the muscles of the stomach is important for normal gastric motility and is impaired in motility disorders. Coordinated electrical depolarizations that originate and propagate within a network of interconnected layers of interstitial cells of Cajal (ICC) and smooth muscle (SM) cells of the stomach wall as a slow-wave, underly peristalsis. Normally, the gastric slow-wave oscillates with a single period and uniform rostrocaudal lag, exhibiting network entrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
(240 reference statements)
0
3
0
Order By: Relevance
“…Using this clever approach, it is possible to monitor the evolution of salivary uric acid during appropriate drug treatment over four consecutive days. In the gastrointestinal tract, biodegradable origami-based robots that can be ingested into the stomach have been deployed that locomote to a desired location, remove a foreign body, patch a wound, deliver drugs, and eventually biodegrade [208,209]. Microrockets are similar microdevices that are composed of poly (aspartic acid) microtubes, thin Fe intermediate layers, and Zn cores.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Using this clever approach, it is possible to monitor the evolution of salivary uric acid during appropriate drug treatment over four consecutive days. In the gastrointestinal tract, biodegradable origami-based robots that can be ingested into the stomach have been deployed that locomote to a desired location, remove a foreign body, patch a wound, deliver drugs, and eventually biodegrade [208,209]. Microrockets are similar microdevices that are composed of poly (aspartic acid) microtubes, thin Fe intermediate layers, and Zn cores.…”
Section: Other Applicationsmentioning
confidence: 99%
“…The coupling is achieved through gap junction models which are typically Ohmic resistor in a network. A recent paper by Ahmed et al (2021) demonstrated this for gastric cells but the approach has been used in other biological modeling. For example, models of uterine electrophysiology used 10.3389/fnins.2023.1146097 a grid lattice network with gap junction coupling to explore organ level bioelectrical propagation (Xu et al, 2015).…”
Section: Whole-organ Electrophysiology Modelsmentioning
confidence: 99%
“…Although initially recommended through a 2-stage approach, LSG has later modified as a stand-alone one step procedure for the treatment of morbid obesity [11]. In LSG, the stomach [12,13] is reduced in capacity by removing two-thirds of the organ and suturing the remaining part using a stapling device. Several studies have supported that LSG showed similar weight loss and reduction in obesity-related comorbidities to LRYGB [14,15].…”
Section: Introductionmentioning
confidence: 99%